Ecosystem controlling as a solution to complex task of optimizing the technological process of industrial production - I. A. Loskutov; V. G. Iskandarova (Омский научный вестник)
The article is devoted to the study of ecosystem controlling and divided into three structural sections. The study is of an overview nature, aimed at popularizing ecosystem approaches in the domestic industry. The main methods of scientific research are systematization and analysis. The introduction provides evidence of the need to search for new solutions to optimize and improve modern domestic industry. The first section analyzes definitions related to the ecosystem. It is considered from the classical (biological) point of view and from the point of view of application in industry. The evidence base of the justification of this approach is given. The second section is devoted to the problems present in industrial ecosystems. The list of the most significant features caused by staff misunderstanding of new approaches is made and the unjustifiability of outdated methods of production organization used everywhere is argued. At the same time, the section focuses on the importance of the manager who is responsible for the functioning of departments and specifies the characteristics required for him. The third section shows the importance of ecosystem controlling as a way to solve the described problems. As evidence, it is divided into two obvious components — technical and human. The direction of the Internet of Things as an integral part of the industrial ecosystem is noted. As a solution to the human component, an example of implementation for little-changing systems is given and recommendations are given for systems of a different nature. In conclusion, the supporting facts of the correctness of the conclusions are given.